2001
DOI: 10.1029/2000jd900267
|View full text |Cite
|
Sign up to set email alerts
|

Cloud‐aerosol interactions during autumn over Beaufort Sea

Abstract: Abstract. Cloud and aerosol properties were observed by aircraft in autumn over the Beaufort Sea during the 1994 Beaufort and Arctic Storms Experiment (BASE). The microphysical properties (particle size, concentration, mass, and phase) and vertical structure of autumn clouds are examined as a function of height and minimum in-cloud temperature, rmi n. Below 2 km, liquid clouds were observed at rmi n between -5 ø and-9øC, mixed-phase clouds were observed between -5 ø and -20øC, and clear-sky ice crystal precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 39 publications
5
45
0
Order By: Relevance
“…For cloud top temperatures below −20 • C, IWP and LWP reach values close to 30 and 50 g m −2 , respectively. The IWP decreases dramatically when the cloud top temperature increases; very low values close to 0 are encountered at temperatures above −8 • C. LWP reaches a maximum of 100 g m −2 at −13 • C and the smallest values (around 15 g m −2 ) are encountered when the cloud top temperature is typically around −18 • C. These findings are consistent with the main previous studies devoted to Arctic MPCs Pinto, 1998;Pinto and Curry, 2001;Shupe et al, 2006). They reported mean LWP values in the range of 20-70 g m −2 , with some maxima up to around 130 g m −2 , and IWP mean values less than 40 g m −2 .…”
Section: Ice and Liquid Water Contents And Integrated Pathssupporting
confidence: 92%
“…For cloud top temperatures below −20 • C, IWP and LWP reach values close to 30 and 50 g m −2 , respectively. The IWP decreases dramatically when the cloud top temperature increases; very low values close to 0 are encountered at temperatures above −8 • C. LWP reaches a maximum of 100 g m −2 at −13 • C and the smallest values (around 15 g m −2 ) are encountered when the cloud top temperature is typically around −18 • C. These findings are consistent with the main previous studies devoted to Arctic MPCs Pinto, 1998;Pinto and Curry, 2001;Shupe et al, 2006). They reported mean LWP values in the range of 20-70 g m −2 , with some maxima up to around 130 g m −2 , and IWP mean values less than 40 g m −2 .…”
Section: Ice and Liquid Water Contents And Integrated Pathssupporting
confidence: 92%
“…A major finding of these experiments was the observed frequency and persistence of supercooled liquid water and mixed-phase stratiform clouds throughout the year Pinto et al, 2001;Intrieri et al, 2002;Shupe and Intrieri, 2004). In contrast to midlatitude cloud systems, there is little temperature dependence for the amount of liquid versus ice in Arctic mixed-phase clouds McFarquhar and Cober, 2004;Turner, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Currently, cloud parameterizations distinguish ice and liquid phase of mixed-phase clouds mainly as a function of temperature alone and are in need of improvement of Arctic cloud parametrization (Vavrus and Waliser, 2008). On the other hand measurements have shown that the liquid water content at low temperatures is sometimes higher than expected and that apart from temperature other parameters such as cooling rates must be considered as well (Pinto et al, 2001). The influence of Arctic aerosol on the climate and radiation budget has been discussed in Treffeisen et al (2005) and Rinke et al (2004).…”
Section: Introductionmentioning
confidence: 99%